MUSIC TRANSFER AND CULTURAL CONTACT: ROMANIAN POPULAR SONGS IN THE REPERTOIRE OF THE SAXONS FROM THE SECAȘE VALLEY - CONSTANTINIU, Theodor (Studia Universitatis Babes-Bolyai Musica, 2022)
The Secașe Valley is an ethnographic area populated by different ethnic groups, the most numerous being the Romanians, Saxons, Hungarians, and Roma. Starting from field recordings of Romanian music performed by Saxon peasants from this region, we aim to contribute to the topic of inter-ethnic musical exchange in Transylvania. The songs borrowed by the Saxons from their Romanian neighbors are diverse, ranging from ritual songs, ballads, lyric songs representative for the area, to dance songs, romances, and other modern creations. We concluded that the Saxons thoroughly absorbed the style of traditional Romanian music not only from their own villages, but also from a wider area that goes past the Secașe Valley and into the neighboring regions. This allows us to claim that, as an ethnic minority, the Saxons were involved in a process of acculturation. The cultural strategy adopted by the Saxon community was the integration within the dominant culture, but without abandoning its own musical patrimony. REZUMAT. TRANSFER CULTURAL ȘI CONTACT MUZICAL: CÂNTECE POPULARE ROMÂNEȘTI ÎN REPERTORIUL SAȘILOR DE PE VALEA SECAȘELOR. Valea Secașelor este o regiune etnografică locuită de diverse grupuri etnice, cele mai numeroase fiind Românii, Sașii, Maghiarii și Romii. Pornind de la înregistrări de teren cu muzică românească interpretată de țărani sași din această regiune, ne propunem să contribuim la studierea relațiilor muzicale interetnice din Transilvania. Cântecele împrumutate de sași de la vecinii lor români sunt diverse, de la creații rituale, la balade, cântece propriu-zise reprezentative pentru arealul discutat, cântece de joc, romanțe sau alte producții moderne. Pornind de la analiza materialelor muzicale disponibile, concluzionăm că unii dintre reprezentanții comunității săsești și-au însușit stilul muzicii tradiționale românești atât din satele de reședință, cât și din arealul mai extins al zonelor învecinate. Acest fapt ne permite să susținem că, în perioada înregistrării cântecelor discutate aici, sașii de pe Valea Secașelor erau implicați într-un proces de aculturație. Strategia culturală adoptată de comunitatea săsească în acest proces a fost aceea de integrare în cultura dominantă, fără ca acest lucru să însemne abandonarea patrimoniului muzical propriu. Cuvinte cheie: sași, Valea Secașelor, schimb cultural, relații interetnice, aculturație, cântece populare românești, Ardealul de sud.